2014
DOI: 10.1371/journal.pgen.1004664
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Induced Stabilization of EIN3/EIL1 Confers Salinity Tolerance by Deterring ROS Accumulation in Arabidopsis

Abstract: Ethylene has been regarded as a stress hormone to regulate myriad stress responses. Salinity stress is one of the most serious abiotic stresses limiting plant growth and development. But how ethylene signaling is involved in plant response to salt stress is poorly understood. Here we showed that Arabidopsis plants pretreated with ethylene exhibited enhanced tolerance to salt stress. Gain- and loss-of-function studies demonstrated that EIN3 (ETHYLENE INSENSITIVE 3) and EIL1 (EIN3-LIKE 1), two ethylene-activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
240
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(246 citation statements)
references
References 63 publications
(109 reference statements)
4
240
1
1
Order By: Relevance
“…In this respect, the possibility exists that the positive or negative regulation of Fe uptake depends on a competition between the positive regulators EIN3/EIL1 and the negative regulator ZAT12 for the same interaction site in the C terminus of FIT. Additionally, the ZAT12 promoter is a direct target of EIN3 (Peng et al, 2014), which hints toward the existence of multiple level connections between the regulators involved in the FIT interaction network.…”
Section: Zat12 Is Part Of the Fit Interaction Network And Exerts A Nementioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, the possibility exists that the positive or negative regulation of Fe uptake depends on a competition between the positive regulators EIN3/EIL1 and the negative regulator ZAT12 for the same interaction site in the C terminus of FIT. Additionally, the ZAT12 promoter is a direct target of EIN3 (Peng et al, 2014), which hints toward the existence of multiple level connections between the regulators involved in the FIT interaction network.…”
Section: Zat12 Is Part Of the Fit Interaction Network And Exerts A Nementioning
confidence: 99%
“…zat12 loss-of-function plants exhibited higher sensitivity to light, H 2 O 2 , salinity, osmotic, and heat stress, whereas overexpression of ZAT12 conferred tolerance to high-light, oxidative, osmotic, and cold stress (Rizhsky et al, 2004;Davletova et al, 2005b;Vogel et al, 2005). ZAT12 was identified as a direct target of EIN3, and ZAT12 transcript levels were up-regulated in EIN3ox (Peng et al, 2014).…”
mentioning
confidence: 99%
“…The top 1000 downregulated genes in mutant plants showed at least 2.1-fold lower expression levels than in the wild type (Supplemental Data Set 11). Strikingly, 457 (45.7%) of these genes were salt induced (Kilian et al, 2007) (Supplemental Data Set 12), and some of them, including DFR, PHI1, or CNI1, have been described to be positive regulators of Arabidopsis tolerance to high salt (Cui et al, 2014;Peng et al, 2014). qPCR experiments confirmed that the expression of these and other salt-regulated genes was lower in lsm1a lsm1b than in wild-type plants after salt treatment, validating once again the RNA-seq data ( Figure 3D).…”
Section: The Arabidopsis Lsm Cytoplasmic Complex Differentially Regulmentioning
confidence: 99%
“…3A). High salinity enhances proteasomal degradation of F-box proteins EBF1/2, resulting in the accumulation of EIN3/EIL1 proteins, which then activate expression of salt tolerance genes Zhang et al, 2011;Peng et al, 2014), as well as peroxidase genes whose products scavenge reactive oxygen species to reduce the damage imposed by high salt (Peng et al, 2014).…”
Section: Ein3/eil1 Are An Integration Node For Signal Cross Talkmentioning
confidence: 99%